Interjurisdictional Variance in US Workers’ Benefits for Emergency Response Volunteers - Van Nostrand, Elizabeth; Pillai, Nandini; Ware, Alix (American journal of public health (1971), 2018)
Volunteers who are deployed during times of disaster are critical public health system assets. These individuals share concerns about a variety of subjects with public health law implications, including whether they are entitled to employment benefits before, during, and after disaster response. We examined and analyzed state employment benefit laws pertaining to emergency response volunteers. We used the Emergency Law Inventory (ELI; https://legalinventory.pitt.edu )—an informatics tool developed at the University of Pittsburgh Graduate School of Public Health that contains more than 1300 statutory and regulatory provisions affecting volunteer activities—to access certain employment laws in 60 jurisdictions. Analyses of the laws revealed that fewer than half of the jurisdictions have laws that protect seniority, vacation time, sick time, or overtime privileges. Additionally, there is tremendous variance and lack of uniformity among the jurisdictions concerning employment status requirements, geographic constraints, time limitations, and economic impacts. Major disasters often necessitate interjurisdictional response. To facilitate effective deployment of volunteers, employment laws should be uniform across the states. Furthermore, limitations that impede volunteer responders should be eliminated.